2019
DOI: 10.18502/jnfs.v4i4.1720
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Chitosan-Based Edible Film Containing Oregano Essential Oil on the Shelf-Life Extension of Fresh Chicken Meat

Abstract: Background: The aim of this study was to investigate the effects of chitosan coatings, oregano essential oil, and their combination on microbial quality of chicken fillet during 12 days in refrigerator temperature. Methods: Oregano oil was extracted by water distillation and then different concentrations of oregano oil (1% and 2%) were used for film preparation. Microbiological tests were carried out on the chicken fillet samples stored in 4 °C at different intervals including days 0, 3, 6, 9, and 12. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…These outputs are in accordance with previous investigations that stated the diminution of Pseudomonas spp. in fresh meat coated with chitosan and EOs [38,58]. These results are also in agreement with Mehdizadeh and Langroodi [8] study which showed strong antibacterial effect of chitosan containing both propolis extract and Zataria multiflora EO.…”
Section: Pseudomonads Countssupporting
confidence: 91%
See 2 more Smart Citations
“…These outputs are in accordance with previous investigations that stated the diminution of Pseudomonas spp. in fresh meat coated with chitosan and EOs [38,58]. These results are also in agreement with Mehdizadeh and Langroodi [8] study which showed strong antibacterial effect of chitosan containing both propolis extract and Zataria multiflora EO.…”
Section: Pseudomonads Countssupporting
confidence: 91%
“…Similar results have been observed for beef packed in chitosan-starch film containing pomegranate peel extract and Thymus kotschyanus EO which were enhanced by increasing their concentrations [55]. Karimnezhad et al [38] also reported that the increase rate of TVC in groups of chicken fillet treated with chitosan film containing oregano EO were notably lower compared to the control and chitosan alone groups.…”
Section: Storage ɵMe (Day) C Ch Ch-o Ch-gse 1% Ch-gse 2% Ch-gse 1%-o Ch-gse 2%-osupporting
confidence: 72%
See 1 more Smart Citation
“…The addition of 1 and 2% oregano EO in chicken meat coated with chitosan stored for 6 d at refrigeration temperatures resulted in a TPC decrease of 1.0 and 1.1 log cfu/g, respectively. Meanwhile, no significant decrease in TC was observed (< 0.5 log cfu/g) ( Karimnezhad et al, 2019 ). In another study, the EOs of summer savory and Shirazi thyme were incorporated in basil seed gum coatings used on chicken fillets which were stored for 8 d at refrigeration temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken meat is an animal protein widely consumed by the population. Fresh chicken meat is highly susceptible to spoilage, and can be a perfect medium for microbial growth (Karimnezhad et al, 2019). Therefore, its preservation requires specialised packaging systems, during the distribution or transportation process till consumption, to maintain the quality of fresh chicken meat.…”
Section: Introductionmentioning
confidence: 99%